Penguatan Daya Saing Industri Gerabah melalui Model Keuangan Terintegrasi - , Nelly; , Sufitrayati; Bakri, Muhammad; Amni, Chairul; Ikhbar, Samsul; Husna, Asmaul (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
The pottery industry, as part of the craft subsector within the creative economy, plays an important role in strengthening MSMEs and local economic development, yet it continues to face significant competitiveness challenges. These challenges are not only related to technological limitations and market access, but also to weak financial management practices that remain fragmented and short-term oriented. This review article aims to systematically examine the role of integrated financial models in enhancing the competitiveness of the pottery industry. Using a literature review approach, this study synthesizes prior research on MSME financial management, cost efficiency, cash flow, investment planning, and business performance. The findings indicate that integrating financing, cost control, cash flow management, and investment planning contributes positively to operational efficiency, product quality, market access, and business sustainability. This article contributes theoretically by positioning finance as a strategic system rather than a purely administrative function in strengthening pottery industry competitiveness. Practical and policy implications highlight the importance of financial literacy, inclusive financing support, and financial digitalization to facilitate the effective and sustainable implementation of integrated financial models.